Computer-Assisted Mandibular Reconstruction using a Patient-Specific Reconstruction Plate Fabricated with Computer-Aided Design and Manufacturing Techniques - Wilde, Frank (Thieme Medical Publishers, 2014)
We investigated the workflow of computer-assisted mandibular reconstruction that was performed with a patient-specific mandibular reconstruction plate fabricated with computer-aided design and computer-aided manufacturing (CAD/CAM) techniques and a fibula flap. We assessed the feasibility of this technique from virtual planning to the completion of surgery. Computed tomography (CT) scans of a cadaveric skull and fibula were obtained for the virtual simulation of mandibular resection and reconstruction using ProPlan CMF software (Materialise(®)/DePuy Synthes(®)). The virtual model of the reconstructed mandible provided the basis for the computer-aided design of a patient-specific reconstruction plate that was milled from titanium using a five-axis milling machine and CAM techniques. CAD/CAM techniques were used for producing resection guides for mandibular resection and cutting guides for harvesting a fibula flap. Mandibular reconstruction was simulated in a cadaveric wet laboratory. No problems were encountered during the procedure. The plate was fixed accurately to the residual bone without difficulty. The fibula segments were attached to the plate rapidly and reliably. The fusion of preoperative and postoperative CT datasets demonstrated high reconstruction precision. Computer-assisted mandibular reconstruction with CAD/CAM-fabricated patient-specific reconstruction plates appears to be a promising approach for mandibular reconstruction. Clinical trials are required to determine whether these promising results can be translated into successful practice and what further developments are needed.